Database nurse staffing indicators: explaining risks of staff job dissatisfaction in outpatient care. (30th December 2013) - Kaunonen, Marja; Salin, Sirpa; Aalto, Pirjo
<x xml:space="preserve">Abstract</x> Aim To explore factors associated with nursing intensity, work environment intensity and nursing resources that may affect nurse job satisfaction and risk of dissatisfaction in outpatient care at one university hospital in Finland. Background Much research has been done to study how nursing intensity, work environment intensity and nursing resources are associated with nurse job satisfaction, but not in the context of outpatient care. Methods This research used a cross‐sectional design. The data were collected from the hospital information systems of outpatient units (n = 12) in autumn 2010. Results Management style showed a statistically significant association with job satisfaction. The risk of dissatisfaction increased when nursing staff had no influence over the design of their jobs, when conflicts and contradictions were not addressed in the workplace and when feedback was not processed. Conclusions Nursing intensity and work environment intensity had no effect on nurse job satisfaction. Nursing resources and patient satisfaction, on the other hand, were important to nurses' job satisfaction. Implications for nursing management The results indicate that nursing management should involve nursing staff in the development of their jobs and the care delivery model.